Hubungan Gaya Belajar Visual dengan Prestasi Belajar Siswa Kelas V SD Negeri 24 Macanang - mUSFIRAH mUSFIRAH; Adnan K Adnan K; Muh. Idris Jafar (Universtas Negeri Makassar, 2022)
; This research is a correlational quantitative research that aims to determine the relationship between of visual learning styles and learning achievement of grade five at SD Negeri 24 Macanang. The data in this study were collected by questionnaire and documentation and processed using descriptive statistical analysis and inferential analysis. The results showed that there was a significant relationship between of visual learning styles and learning achievement grade five at SD Negeri 24 Macanang with a r value of (0,273) greater (>)rtableÂ value (0,263) which means H0 is rejected and H1 is accepted. Based on the results of the study, it can be concluded that the visual learning styles will have an impact on students' learning achievement. So the better the visual learning styles, the better the students' learning achievement. From these conclusions, the impact resulting from this study is known that visual learning styles will increase students' learning achievement.